(untitled) (Research, Society and Development, 2023)
This article aims to contribute to the theoretical accumulation of Social Work regarding the professional work based on the experience of three students in their experience in the mandatory supervised internship in Social Work I and II with a focus on the intervention project developed. It consists of a descriptive study, with a qualitative bias, in the form of an experience report referring to the experience in relation to the mandatory supervised internship in Social Work, dated from March to December 2022, in which the students were allocated at the Maternidade Divino Amor Hospital, located in Parnamirim/RN, working 12 hours a week. In view of the observations made during the first semester of activities, the students chose as the theme of the intervention project the fight against female overestimation in the exercise of parental responsibilities. To objectify it, the postpartum women from two sectors of the establishment were approached, individually, with the purpose of discussing the female overload in the exercise of parenthood as well as the paternal and state responsibility in the development process of children and adolescents. In addition, some children’s rights and information about how to access them through articulation with public bodies available in the city of Parnamirim were listed. Based on the experience, the undergraduates had the opportunity to try out a kind of professional intervention in order to show an example of the potential contribution that Social Work can offer in the direct care of puerperal women in a health establishment.